2020
DOI: 10.1021/acs.energyfuels.0c02904
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Combustion and Microexplosion Characteristics of N-Alkane Droplets

Abstract: A detailed experimental investigation on the effect of thermal properties on single droplet combustion characteristics has been performed at room temperature and atmospheric pressure under normal gravity with four n-alkanes (n-octane, n-dodecane, n-tetradecane, and n-hexadecane). The evolution of suspended droplet diameter and the global flame over time were obtained using microscopic and direct photography simultaneously. The results show that the n-alkane droplets used in this study exhibited similar D 2-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
6
0
4
Order By: Relevance
“…Its diameter evolution curves present instabilities (discrete diameter variations) as a result of the ejection of volatiles inside the droplet. 28 According to the literature, it can be theorized that, after the heating period is achieved and the flame is established, the gasification is sustained by the co-vaporization of different components. 11 During this process, some of the most volatile components remain trapped inside the core of the droplet as a result of liquid-phase diffusional resistance and could become superheated, leading to the nucleation of gas bubbles and the subsequent violent rupturing of the droplet in the form of puffing or microexplosions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its diameter evolution curves present instabilities (discrete diameter variations) as a result of the ejection of volatiles inside the droplet. 28 According to the literature, it can be theorized that, after the heating period is achieved and the flame is established, the gasification is sustained by the co-vaporization of different components. 11 During this process, some of the most volatile components remain trapped inside the core of the droplet as a result of liquid-phase diffusional resistance and could become superheated, leading to the nucleation of gas bubbles and the subsequent violent rupturing of the droplet in the form of puffing or microexplosions.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of the droplets of the fuel mixture with 75% Jet A-1 shows the most distinctive behavior because of the occurrence of puffing and microexplosions. Its diameter evolution curves present instabilities (discrete diameter variations) as a result of the ejection of volatiles inside the droplet . According to the literature, it can be theorized that, after the heating period is achieved and the flame is established, the gasification is sustained by the co-vaporization of different components .…”
Section: Resultsmentioning
confidence: 99%
“…Then the bubbles nucleate and grow, finally breaking through the action of droplet surface tension and causing puffing or breaking. Shang et al [37] investigated the combustion and micro-explosion characteristics of n-alkane droplets, and they found that micro-explosion is strongly occurring when the components are sufficiently different in thermal properties and the concentrations of all components are equivalent. The effect of pressure on micro-explosion remains highly controversial.…”
Section: Introductionmentioning
confidence: 99%
“…They determined the intensity of soot expressed by the KL factor by analyzing the optical spectrum of CCD camera images using two-color thermometry. Other researchers ,,,, have also studied the characteristics exhibited by droplets in combustion, but the optical diagnostic capabilities in these studies were limited to blackbody radiation by soot. It is worth noting that the spontaneous radiation signal is accumulated from different radii of the droplet flame, and the morphological changes of the flame (which are common in droplet combustion) can very easily interfere with the signal.…”
Section: Introductionmentioning
confidence: 99%